2007
DOI: 10.1007/s00442-007-0919-4
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator-mediated selfing in two deceptive orchids and a review of pollinium tracking studies addressing geitonogamy

Abstract: Among the factors thought to have favoured the evolution of deception (rewardlessness) in orchids is the reduction of pollinator-mediated selfing when unrewarded pollinators visit fewer flowers per inflorescence. We obtained data on natural levels of geitonogamy in the deceptive orchids Dactylorhiza sambucina and Himantoglossum hircinum by monitoring the dispersal and receipt of colour-coded pollinia. As donors, we marked 185 flowers of D. sambucina and 956 flowers of H. hircinum. In D. sambucina, 30% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…Studies elsewhere directly tracking pollen and using molecular markers to assign pollen to parental plants have revealed that there is no simple dichotomy between bird pollination and insect pollination in terms of pollen movement, with several groups of insects moving pollen considerable distances (Nason et al 1998;Hanson et al 2008;Pasquet et al 2008). However, those species where small pollen movement distances have been reported are predominantly insect-pollinated herbs (Kropf & Renner 2008;Llaurens et al 2008).…”
Section: The Swafr Landscape and The Evolution Of Pollination Systemsmentioning
confidence: 99%
“…Studies elsewhere directly tracking pollen and using molecular markers to assign pollen to parental plants have revealed that there is no simple dichotomy between bird pollination and insect pollination in terms of pollen movement, with several groups of insects moving pollen considerable distances (Nason et al 1998;Hanson et al 2008;Pasquet et al 2008). However, those species where small pollen movement distances have been reported are predominantly insect-pollinated herbs (Kropf & Renner 2008;Llaurens et al 2008).…”
Section: The Swafr Landscape and The Evolution Of Pollination Systemsmentioning
confidence: 99%
“…In addition, Vöth (1990) argued that the dense papillae that partially obscure the spur entrance may secrete tiny drops of nectar, and several subsequent authors have also at least tentatively inferred the presence of a small nectar reward in H. hircinum (Neiland et al, 2001;Bournérias & Prat, 2005;Inda et al, 2012). In truth, such allegations could be levelled against any food-deceitful species of Orchidinae; there is little doubt that pollinators of Himantoglossum species receive no meaningful reward Kropf & Renner, 2008;Claessens & Kleynen, 2011;Bateman, 2013).…”
Section: Pollination Biologymentioning
confidence: 99%
“…However, the occurrence of at least some geitonogamy (cross-pollination of genetically identical flowers occupying the same inflorescence) was confirmed long ago by the fact that even solitary flowering plants often set seed (Summerhayes, 1951). More recently, detailed observations by Kropf & Renner (2008) estimated a geitonogamy frequency of 36% in three populations of Lizard Orchid in southern Germany. As concluded by Kropf & 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Renner (2006, p. 506), "foraging behaviour results in a mix of geitonogamy, nearneighbour pollination, and occasional long-distance outcrossing not fundamentally different from the situation in many other insect-pollinated perfect-flowered rewarding angiosperms."…”
Section: Pollination Biologymentioning
confidence: 99%
See 2 more Smart Citations